Heat shock protein gene expression profile may differentiate between rheumatoid arthritis, osteoarthritis, and healthy controls - Sedláčková, Lucie; Sosna, Antonín; Vavřincová, Pavla; Frýdl, Jiří; Guerriero, V; Raynes, D A; Hromadníková, Ilona (Scandinavian journal of rheumatology, 2011)
OBJECTIVE: Heat shock proteins (Hsps) have been repeatedly implicated in the pathogenesis of rheumatoid arthritis (RA). The aim of this work was to study Hsp mRNA and protein levels to determine whether they can be used to differentiate between RA, osteoarthritis (OA), and healthy controls. METHODS: Hsp27, Hsp60, Hsp70, Hsp90α, and HspBP1 mRNA expression was analysed using real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR) in 24 RA, 11 OA, and 21 healthy controls. Hsp70 and HspBP1 protein levels were measured in serum using an enzyme-linked immunosorbent assay (ELISA). RESULTS: Hsp gene expression profiles differ significantly between inflammatory (RA) and non-inflammatory (OA) joint diseases, showing significantly increased Hsp27 and Hsp90α mRNA levels in RA synovial tissues. Up-regulated Hsp60 and Hsp90α together with down-regulated Hsp70 and elevated HspBP1/Hsp70 mRNA ratios can be used to differentiate between RA patients and healthy individuals through analysis of peripheral blood samples. Despite increased HspBP1 levels in RA sera, Hsp70 levels and the HspBP1/Hsp70 protein ratio remained identical in the RA patients and healthy individuals, which may contribute to the inhibition of Hsp70 anti-apoptotic activity. CONCLUSION: Hsp gene expression analysis can be implemented as a new diagnostic approach to facilitate differentiation between RA, OA, and healthy controls.
Keywords: diferenciální diagnóza; Arthritis, Rheumatoid; osteoartróza; Female; revmatoidní artritida; ženské pohlaví; Up-Regulation; Heat-Shock Proteins; lidé; upregulace; Synovial Membrane; stanovení celkové genové exprese; synoviální membrána; Diagnosis, Differential; kohortové studie; Cohort Studies; Down-Regulation; Male; Aged; Osteoarthritis; lidé středního věku; down regulace; senioři; mužské pohlaví; Middle Aged; Gene Expression Profiling; proteiny teplotního šoku; Humans